Some considerations on China's minorities in the 21st century: Conflict or conciliation? - Thomas Heberer (Gerhard-Mercator-Universität Duisburg, Institut für Ostasienwissenschaften, 2000)
On a global scale, there has been a significant increase of ethnic conflicts in the last decade. They constitute one of the main sources of domestic political instability in multi-national countries. Recent opinion polls among Chinese citizens point to growing ethnic conflicts even in China. This paper addresses primarily five sources of conflict: collective memory, political conflicts, economic conflicts, cultural conflicts and new conflicts arising from economic and social change. It explores various forms of ethnic resistance (active and passive ones, violent and peaceful ones, formal and informal patterns) and suggests possible measures of conflict prevention and reduction of conflicts. Finally it argues that China may provide a good basis for such measures, as ethnic minorities are not only recognized as nationalities, but also are respected by public law and - according to this law - enjoy the same rights as the ethnic majority.
Keywords: 330; ethnic minorities; ethnic conflict; ethnicity; conflict prevention